INFLUENCE OF RAINFALL AND RELATIVE HUMIDITY ON MORTALITY FROM RESPIRATORY DISEASES: A CASE STUDY FOR THE MUNICIPALITY OF SÃO LUÍS – MA - Buna, Amanda Caroline da Silva; Mendes, Jonas Jansen; Braz, Isabelle Maria Veloso; Chaves, Narla dos Reis Bacelar; dos Anjos, Maria do Rosário Oliveira (Editora Impacto Científico, 2025)
This study aims to analyze the influence of rainfall and relative humidity on mortality from respiratory diseases in São Luís, Maranhão, between July 2021 and June 2024. The research is based on concepts from biometeorology and research on the effects of climate change on public health, which indicate that atmospheric variables can aggravate respiratory diseases in vulnerable groups. This is an exploratory quantitative study based on data on deaths from Respiratory Tract Diseases obtained from the Death Verification Service (SVO), correlated with meteorological information from the Maranhão State University Station. Statistical analysis was performed using Pearson’s correlation and polynomial adjustment. The results reveal no statistically significant association between climate variables and mortality in the general population. However, when specifically focusing on the elderly population (60+), a direct correlation was identified between these climate variables and the increase in deaths. The research reinforces the importance of integrating meteorological data and public health policies, especially during seasonal transitions. This research, with its intersectional approach to climate and urban health, contributes to public policy and prevention strategies. DOI: 10.56238/edimpacto2025.060-003